PENGARUH JAM KERJA TERHADAP KESEHATAN FISIK DAN MENTAL KARYAWAN DI KLINIK FATIMAH KECAMATAN CILAMAYA KULON KABUPATEN KARAWANG - Chaerani Tri Yuliana; Wieke Widhiantika; Jumaedi, Jumaedi; Muhidin, Muhidin; Wendi Darmawan (Bajang Institute, 2023)
This study aims to analyse the impact of working hours on the physical and mental health of employees at Klinik Fatimah, located in Cilamaya Kulon District, Karawang Regency. Using a quantitative approach and a cross-sectional research design, data were collected from employees through standardized questionnaires covering aspects of physical fatigue, mental stress, burnout, and cardiovascular disorders. The study results indicate that the majority of employees experience negative impacts from long working hours, which not only deteriorate their health but also affect the quality of healthcare services provided to patients. Compared to other clinics in Karawang, such as Klinik Sehat Mandiri and Klinik Harapan Bunda, Klinik Fatimah shows higher levels of physical fatigue and mental stress. This study emphasizes the importance of implementing more balanced working hours, mental health support, and employee wellness programs to improve employee well-being and service quality. This research makes a significant contribution to public health literature, particularly in the Indonesian context, and offers practical recommendations for clinic management